Positive Effect of Visual Cuing in Episodic Memory and Episodic Future Thinking in Adolescents With Autism Spectrum Disorder - Anger, Marine; Wantzen, Prany; Le Vaillant, Justine; Malvy, Joëlle; Bon, Laetitia; Guénolé, Fabian; Moussaoui, Edgar; Barthelemy, Catherine; Bonnet-Brilhault, Frédérique; Eustache, Francis; Baleyte, Jean-Marc; Guillery-Girard, Bérengère (Frontiers in Psychology, 2019)
Cognitive studies generally report impaired autobiographical memory in individuals with autism spectrum disorder (ASD), but mostly using verbal paradigms. In the present study, we therefore investigated the properties of both past and future autobiographical productions using visual cues in 16 boys with ASD and 16 typically developing (TD) participants aged between 10 and 18 years. We focused on sensory properties, emotional properties, and recollection, probing past and future productions for both near and distant time periods. Results showed that the ASD group performed more poorly than controls on free recall for recent periods, but performed like them when provided with visual cues. In addition, the ASD group reported fewer sensory details than controls and exhibited difficulties in the experience of recollection for the most remote events. These data suggest a combination of consolidation and binding deficits. Finally, our findings reveal the relevance of using visual cues to probe autobiographical memory, with possible perspectives for memory rehabilitation.